Development of a Leachate Processing Practicum Module Using the 4D Model to Support Scientific Literacy in Junior High School Students - Rendra Cipta; Eko Risdianto; Arsela Eko Listiono; Henny Johan; Bhakti Karyadi; Deni Parlindungan; Mehdi Manoochehrzadeh; Hamed Barjesteh (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2026)
Background: The integration of environmental issues into junior high school science learning remains limited, reducing opportunities for students to develop scientific literacy through contextual, practical activities. Although science literacy-oriented modules have been developed, practicum modules that focus on converting leachate into liquid organic fertilizer as a contextual learning resource for scientific literacy are still rarely reported.Aim: This investigation sought to create and assess the practicability of a leachate-processing practicum module intended to support scientific literacy among students in junior high school. Methods: The investigation utilized a research and development methodology employing the 4D model, which encompasses the Define, Design, and Develop phases. A restricted implementation was carried out utilizing a one-group pretest–posttest framework. Validation involved four experts. Participants were Grade IX students: 27 completed the response questionnaire and 24 the scientific literacy test, reflecting attendance during the respective data collection sessions. Data were examined utilizing Aiken’s V, descriptive statistics, N-gain, and a paired-sample t-test.Results: The module demonstrated high validity with an Aiken’s V score of 0.961. Student responses exceeded 90%, indicating very positive perceptions of the module. Scientific literacy scores demonstrated an increase from a mean pretest score of 59.17 to a mean posttest score of 89.58, accompanied by an average N-gain of 0.79, which is classified within the high category. Significant differences were found between pretest and posttest scores (p < 0.001).Conclusion: The developed practicum module is feasible for use in contextual science learning and demonstrates promising effects on students’ scientific literacy in a limited implementation setting.